Ribociclib plus endocrine therapy in bone marrow visceral crisis: challenging the chemotherapy paradigm in luminal metastatic breast cancer—a case report - Pérez-López, Oscar Ivan; Lendinez-Sanchez, Gonzalo; González-García, Jesús; Jiménez-Rodríguez, Begoña; Leon-Fradejas, Myriam; Fernandez-Garay, David (Frontiers in Oncology, 2025)
IntroductionVisceral crisis in hormone receptor-positive (HR+), HER2-negative metastatic breast cancer poses a therapeutic challenge, traditionally managed with chemotherapy due to the urgency of organ dysfunction. However, recent evidence suggests that cyclin-dependent kinase 4/6 inhibitors (CDK4/6i), in combination with endocrine therapy (ET), may offer rapid and effective disease control even in aggressive presentations.Case presentationWe report the case of a 52-year-old premenopausal woman diagnosed with de novo HR+, HER2-negative metastatic lobular breast cancer presenting with severe anemia and thrombocytopenia secondary to diffuse bone marrow infiltration. The patient was initially managed with letrozole and goserelin, followed by the addition of ribociclib. Clinical and hematologic parameters improved rapidly, and the patient achieved a complete metabolic response after nine treatment cycles without significant toxicity.DiscussionThis case highlights bone marrow infiltration as a form of visceral crisis, reinforcing the heterogeneity of visceral crisis presentations beyond solid organ involvement. The rapid response and sustained disease control observed with CDK4/6i plus ET challenge the traditional paradigm favoring chemotherapy in such scenarios. Supporting evidence from RIGHT Choice, ABIGAIL, and recent case series further validates this therapeutic approach in carefully selected patients.ConclusionCDK4/6 inhibitors in combination with endocrine therapy may constitute an effective and well-tolerated alternative to chemotherapy in HR+/HER2− metastatic breast cancer presenting with visceral crisis, including hematologic compromise due to bone marrow involvement. This case underscores the need to reconsider current treatment algorithms to include targeted therapies as a viable and effective option in acute and life-threatening presentations of HR+/HER2− metastatic breast cancer.